Cake Rasida As Representation Identity Malay Ethnic Culture At Wedding Ceremonies In Langkat Regency - Nadya Shahrani; Sulian Ekomila (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
The tradition of eating rice face-to-face during Langkat Malay wedding ceremonies is a form of cultural expression rich in symbolism and social values. A crucial element of this tradition is the rasida cake, which serves not only as a dish but also holds profound symbolic meaning. This research aims to reveal the meaning of rasida cake in terms of ingredients, manufacturing process and form of presentation in the context of the tradition of eating rice face to face as well as changes in its meaning from time to time. The research method used is qualitative with an ethnographic approach. Data were collected through participant observation, in-depth interviews, documentation, and field notes with informants consisting of the bride and groom's families, traditional leaders, the Malay community, invited guests, and the younger generation in Tanjung Pura District, Langkat Regency. The research results show that rasida cake was originally a sacred dish in the palace environment which functioned as a symbol of honor and unity for the king and the nobles. However, as time goes by, the meaning has shifted to become a symbol of honor and acceptance towards the groom's family and invited guests, as well as a form of cultural preservation in the midst of modern society. The materials, manufacturing process, and presentation forms also undergo transformation without eliminating the symbolic values contained within them. Therefore, Rasida cake is a representation of the cultural identity of the Langkat Malays which reflects dignity, politeness, and the values of togetherness in the social life of the community.